PENINGKATAN KEMAMPUAN LITERASI DAN NUMERASI SISWA SDN 10 KENERAK MELALUI KAMPUS MENGAJAR - Rahman, Tri Wanda; Perdana, Hendra (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2023)
Campus teaching is a program from the Ministry of Education, Culture, Research, and Technology which provides opportunities for students to study off campus for one semester. Through the Teaching Campus program, students have activities that are their responsibility in helping learning activities at school. In this program, students partner with teachers at SDN 10 Kenerak, Semitau District, Kapuas Hulu Regency, West Kalimantan Province. The main task of this teaching campus program is to assist teachers in carrying out learning in schools, in particular to improve literacy and numeracy, increase student creativity and help students adapt to technology. The Teaching Campus Program by sending students as school change agents has helped the implementation of teaching and learning activities.